Formação profissional em Serviço Social na perspectiva da ética profissional e dos Direitos Humanos - Silva, Rosane Durval da (2011)
This study presents an analysis about graduate level training in Social Work from the perspective of professional ethics and human rights. The aim of this work is to analyze whether the graduate level training in Social Work contributes to the understanding of professional ethics and human rights, which permeate the professional daily work. In this way, the research aims not only to understand the professional ethics issue but also to analyze how it permeates the professional daily work, by identifying the subsidies provided in the training process and the relationship between professional ethics and human rights. Thus, the analysis considers the nineties, period in which there was a systematization of ethics for Social Work. In this way, it is used the analysis and publications from the professional category, all of them related to ethics, professional ethics and its fundamental importance to the professional training. In order to understand the elements subsidized by training, three social workers and a Social Work student took part in this research, by giving interviews and necessary contribution not only to understand the training in the perspective of professional ethics and human rights, but also to observe the relationship between their professional daily work and their experience in this area. Finally, the research registers not only the commitment to training, ethics and professional ethics, but also the reflection on human rights as fundamental elements in the construction of the ethical-political project for this professional category